Case report: A rare case of acute hemolysis in advanced rectal cancer after XELOX and nivolumab treatment: analysis of drug-dependent antibodies - Zhao, Dengke; Song, Qiao; Wu, Chunyan; Wang, Shuye (Frontiers in Medicine, 2023)
Objective: To investigate the mechanism, in vitro differential test and clinical significance of hemolytic anemia after receiving oxaliplatin and nivolumab treatment. Methods: We encountered a male patient with stage IV rectal cancer who experienced acute hemolysis during the ninth cycle of treatment with XELOX combined with nivolumab and cetuximab. The patient's blood samples were collected and tested for the presence of oxaliplatin or nivolumab antibodies on red blood cells. Result: Direct antiglobulin testing of red blood cells incubated with oxaliplatin was strongly positive, whereas cells incubated with nivolumab were negative, which suggested that oxaliplatin was responsible for the hemolysis. After short-term highdose glucocorticoid treatment, human normal immunoglobulin infusion, and other symptomatic treatments, the patient’s condition rapidly improved, and he continued to receive nivolumab treatment without further hemolysis. Conclusion: Attention should be paid to the possibility of acute hemolysis when using oxaliplatin and nivolumab, and it is important to recognize and manage this adverse event early. We detected oxaliplatin-related antibodies on the surface of red blood cells in vitro, which provided evidence for the following treatments.